2023
DOI: 10.1038/s41420-023-01336-x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated fibroblast-secreted IGFBP7 promotes gastric cancer by enhancing tumor associated macrophage infiltration via FGF2/FGFR1/PI3K/AKT axis

Abstract: We previously reported that IGFBP7 plays a role in maintaining mRNA stability of oncogenic lncRNA UBE2CP3 by RNA-RNA interaction in gastric cancer (GC). Clinical cohort studies had implied an oncogenic role of IGFBP7 in GC. However, the molecular mechanism of IGFBP7 in GC progression remains unknown. In this study, clinical analysis based on two independent cohorts showed that IGFBP7 was positively associated with poor prognosis and macrophage infiltration in GC. Loss-of-function studies confirmed the oncogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…75 Moreover, EMT signalling can also promote tumour metastasis by regulating the expression of the oncogenic or tumour-suppressive long non-coding RNAs and proteins. 76,77 For instance, it has been reported that the EMT-induced lncRNA NR2F1-AS1 promoted gastric cancer metastasis via miR-29a/VAMP7 axis. 78 The interferon regulatory factor IRF6, which is repressed by EMT signalling, plays a tumour suppressive role in breast and gastric cancer.…”
Section: Emt and Tumour Metastasismentioning
confidence: 99%
“…75 Moreover, EMT signalling can also promote tumour metastasis by regulating the expression of the oncogenic or tumour-suppressive long non-coding RNAs and proteins. 76,77 For instance, it has been reported that the EMT-induced lncRNA NR2F1-AS1 promoted gastric cancer metastasis via miR-29a/VAMP7 axis. 78 The interferon regulatory factor IRF6, which is repressed by EMT signalling, plays a tumour suppressive role in breast and gastric cancer.…”
Section: Emt and Tumour Metastasismentioning
confidence: 99%
“…44 On the one hand, CAFs triggered phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) pathway to induce the polarisation of M2 TAMs by secreting IGFBP7 and POSTN. 48,49 On the other hand, mixed TAMs of M1 and M2 enhanced the cancerpromoting roles of CAFs by increasing the secretion of IL-1β in TME, which accelerated the malignant progression of GC. 50 Moreover, MSCs derived from GC activated the JAK2/STAT3 pathway to enhance the polarisation of M2 TAMs by increasing the secretion of IL-6 and IL-8.…”
Section: The Interactions Between Tams and Diverse Cell Types In Tmementioning
confidence: 99%
“…However, M2 TAMs inhibited the functions of T cells by increasing the accumulation of lipids in TME, thereby causing immune evasion of GC cells 44 . On the one hand, CAFs triggered phosphatidylinositol‐3‐kinase/protein kinase B (PI3K/Akt) pathway to induce the polarisation of M2 TAMs by secreting IGFBP7 and POSTN 48,49 . On the other hand, mixed TAMs of M1 and M2 enhanced the cancer‐promoting roles of CAFs by increasing the secretion of IL‐1β in TME, which accelerated the malignant progression of GC 50 .…”
Section: The Interactions Between Tams and Diverse Cell Types In Tmementioning
confidence: 99%
See 2 more Smart Citations